Metodologia para estimativas de fluxo de calor na peça em operações de fresamento - Barrios, André Nozomu Sadoyama (2018)
One of the most widely used machining processes in the industry is milling. The study of the thermal area in the milling is a challenge, because it is a process in which the cutting occurs in a very specific region of difficult access for its correct measurement. One of the solutions for the analysis of the temperature in the machining process is the use of thermal models solved by mathematical methods that bring good estimates. Currently, besides the software developed in the academic environment, there are also computational tools available in the market. However, commercial software presents closed programming code which makes it difficult to study more specifically for particular cases. Through the search of several authors, both in work in the context of turning and in milling, it was noticed that the use of the inverse resolution method by Gauss-Newton for estimates of heat flow is still very restricted. In the works by Braghini Junior (2002) and by the author himself in Barrios (2013) this method was implemented, but the methodology was only for estimates of the average heat flux, neglecting the variation of the heat flow as a function of the time displacement of the tool . The objective of this work is to develop a new methodology for estimating the heat flux in the part in milling operations considering the effects of tool displacement as a function of time using the GaussNewton method. For this, it was necessary to develop a Thermal Simulator for Machining by Milling (STUF), to analyze the effects of the variables adopted in the simulator and finally to make estimates of heat flux through the experimental temperature data of machining. Two interfaces were created for the STUF, being an interface for the estimations of heat flow and an interface for the temperature estimates in the part. For this purpose, Matlab® was used as a computational environment and as a programming language for simulations. The effects of the variables in the simulator, such as the convective coefficient (h), mesh refining, time step (Δt), part geometry, experimental temperature and error analysis were analyzed. It was possible to estimate heat flux and temperature in the piece by means of the case study 1, using the Braghini (2002) experimental data, case study 2, through the experimental data of Barrios (2013), and case study 3, through the experimental data proposed by this work. This new methodology used by the STUF allowed the identification of the maximum heat flux in the part, allowed the generation of estimated temperature results with good adjustments with the experimental temperatures with mean R² of 0.85 for case study 1 and R² of 0,95 for case study 2. Case study 3 presented many noises, but estimates were possible.